Impact of therapeutic hypothermia (whole body cooling) on severely asphyxiated term neonates: a prospective non-randomized comparative study in an Indian tertiary care setting - Shah, Kruti; Aiyer, Sheila; Singh, Saumitra (International Journal of Contemporary Pediatrics, 2024)
Background: Early application of Therapeutic Hypothermia within 6 hours of birth is neuroprotective. We aimed at examining whether therapeutic hypothermia alongside standard optimal intensive care improves immediate survival outcome and reduces neuro-disability. Methods: This was a prospective non-randomized study involving inborn and out born newborns admitted at NICU, carried out from March 2022 to December 2022. Eligible candidates were enrolled as cases and therapeutic hypothermia was offered while rest were included as a control group and monitored likewise for the overall survival and neurological outcome. These babies were followed up till 1 month and 3 months of age to assess neurological outcome. Results: In this study, a total of 47 patients were enrolled both from extramural and intramural NICU set ups. Of them, 22 patients were offered Therapeutic Hypothermia and 25 patients were given standard post asphyxia care. 7 out of 9 inborn patients and 3 out of 13 out born neonates who were offered therapeutic hypothermia survived whereas 5 out of 11 inborn and 4 out of 14 out born neonates who were offered standard post asphyxia care survived. Conclusions: Therapeutic hypothermia cannot be attributed to significant increase or decrease in mortality when compared with standard care group. No inference could be made about hypothermic neuroprotection in the follow up study. Overall survival outcome was better in inborn patients than that of outborn. Inborn neonates subjected to therapeutic hypothermia, showed a trend towards better survival than those given standard post asphyxia care.